Peningkatan Kapasitas Produksi dan Pemasaran Produk Keripik Pisang Melalui Inovasi Teknologi dan Digitalisasi Usaha di Desa Pati'di - tapion, Rhena; Halim, Abdul; Muhktar; K, Jumiati; Rosita (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
This Community Service Program (PKM) was implemented in Pati’di Village, Simboro District, Mamuju Regency, aiming to enhance the production capacity and marketing performance of banana chips through technological innovation and business digitalization. The partner group, Komunitas Baine Botteng, consists of 11 women micro-entrepreneurs engaged in local banana processing. The program employed a participatory approach encompassing stages of socialization, non-technical training, business digitalization assistance, and ongoing evaluation. Due to equipment delivery delays, the activities primarily focused on strengthening managerial skills, financial literacy, product packaging design, and digital marketing strategies. The results indicate substantial improvement in non-technical aspects. Approximately 83% of participants successfully adopted simple bookkeeping using the BukuKas mobile application, all participants (100%) designed attractive product labels and packaging using Canva, and 73% utilized social media for online product promotion. Beyond technical outcomes, the program also fostered social impacts, including heightened motivation, active participation, and collective awareness among members regarding innovation and entrepreneurship. This empowerment model demonstrates that managerial and digital literacy development serves as a crucial foundation for subsequent adoption of appropriate production technologies. The PKM initiative contributes to sustainable rural economic empowerment and provides a replicable model for other women’s communities to develop competitive local-based enterprises through the synergy of technological innovation, digital transformation, and socio-economic capacity strengthening.